Potret Gaya Hidup Perempuan Urban dalam Novel Metropop To Tokyo To Love karya Mariskova - Reza; Hasanuddin WS, Hasanuddin WS (Universitas Negeri Padang, 2024)
This article aims to describe the portrait of urban women's lifestyles in the metropop novel To Tokyo To Love by Mariskova. This research employs a descriptive literary method. The data used for discussion include words, phrases, clauses, sentences, and dialogue that reflect various aspects of urban women's lifestyles, as conveyed through narration, the narrator, and character actions in To Tokyo To Love by Mariskova. The data collection technique was conducted in four stages: first, reading and comprehending the metropop novel To Tokyo To Love by Mariskova; second, identifying the main and side characters; third, marking sections of the novel that contain lifestyle-related data; and fourth, inventorying the data. Subsequently, the data were classified and analyzed based on the theories of mobility, instant, virtual, and individualist lifestyles. The data were then interpreted, conclusions were drawn, and a report was created. The analysis yielded the following results: (1) portraits of urban women's mobility lifestyle, (2) portraits of urban women's instant lifestyle, (3) portraits of urban women's virtual lifestyle, and (4) portraits of urban women's individualist lifestyle in Mariskova's metropop novel To Tokyo To Love. Among these four portraits, the most dominant is the portrayal of a virtual lifestyle.